Robust reliable H∞ optimization control for uncertain discrete‐time Takagi–Sugeno fuzzy systems with time‐varying delay. (1st March 2021) - Sun, Shaoxin; Zhang, Huaguang; Su, Hanguang; Liang, Yuling
Abstract: In this article, the problems of robust reliable H ∞ optimization control for discrete‐time nonlinear systems with or without time‐delay subject to faults are investigated. A static state feedback controller is explored for Takagi–Sugeno fuzzy systems against nonlinear dynamics, exogenous disturbances, and model uncertainties. In contrast to the design of conventional controllers, the proposed controller is easier and more flexible. The Lyapunov function is utilized to assure the stability of the closed‐loop systems. Besides, linear matrix inequalities are utilized to derive the sufficient conditions by MATLAB toolbox. Finally, two simulation examples are shown to validate the feasibility of the suggested approach.